"Telling It Like It Is ... ": Understanding the Truth and Reconciliation Commission from the Perspective of Survivors - Hamber, Brandon; Nageng, Dineo; O’Malley, Gabriel (PINS-Psychology in Society, 2026)
The article focuses on survivors’ perspectives of the Truth and Reconciliation Commission (TRC). It probes their feelings, thoughts and views both before and after interacting with the Commission. Their feelings and opinions about issues such as justice, punishment and amnesty are explored. This information, which forms the backbone of this article, was obtained from interviews with twenty survivors of political violence committed under the apartheid government. The article shows that healing, truth, justice and reconciliation are interrelated. For survivors the relationships between the concepts is not linear, that is truth does not automatically lead to reconciliation. The article demonstrates that those who interacted with the TRC held a range of largely legitimate expectations; most expected, at the very least, that they would get some truth about their case. Many are currently feeling let down by the TRC process, despite its successes at publicising the atrocities of the past and fostering national reconciliation.